Managing risk taking with interest rate policy and macroprudential regulations - Simona E. Cociuba; Malik Shukayev; Alexander Ueberfeldt (The University of Western Ontario, Department of Economics, 2016)
We develop a model in which a financial intermediary's investment in risky assets - risk taking - is excessive due to limited liability and deposit insurance, and characterize the policy tools that implement efficient risk taking. In the calibrated model, coordinating interest rate policy with state-contingent macroprudential regulations - either capital or leverage regulation, and a tax on profits - achieves efficiency. Interest rate policy mitigates excessive risk taking, by altering the return and the supply of collateralizable safe assets. In contrast to commonly-used capital regulation, leverage regulation has stronger effects on risk taking and calls for higher interest rates.
Keywords: E44; E52; G11; G18; 330; Financial intermediation; risk taking; interest rate policy; macroprudential regulations; capital requirements; leverage ratio